2011
DOI: 10.3748/wjg.v3.i2.95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative staging in advanced gastric cancer with MRI

Abstract: AIM:To evaluate the application o� magnetic resonance imaging (MRI) to the preoperative staging o� advanced gastric cancer. METHODS:An MRI (SE sequence) was preoperatively per�ormed on 34 patients with advanced gastric cancer. The tumors were located at the cardia �undus in 11 patients, the corpus in 14, the antrum in ten and throughout the entire stomach in two. The images were analyzed and staged on the basis o� the criteria proposed by Matsushita M. The results were compared with the corresponding histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The data were available in 8 US studies [ 21 - 27 , 29 ], 2 EUS studies [ 27 , 31 ], 18 CT studies [ 21 - 23 , 27 , 29 , 36 , 39 , 41 , 43 - 51 , 53 ], 2 MRI studies [ 37 , 38 ], and 4 18 F-FDG PET studies [ 35 , 36 , 41 , 42 ]. Meta-analysis was based on the bivariate model in the presence of significant heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were available in 8 US studies [ 21 - 27 , 29 ], 2 EUS studies [ 27 , 31 ], 18 CT studies [ 21 - 23 , 27 , 29 , 36 , 39 , 41 , 43 - 51 , 53 ], 2 MRI studies [ 37 , 38 ], and 4 18 F-FDG PET studies [ 35 , 36 , 41 , 42 ]. Meta-analysis was based on the bivariate model in the presence of significant heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of MRI over CT include the ability of generating significantly greater soft tissue contrast resolution, and the ability of removing the risk of iodinated contrast-induced nephropathy or ionizing radiation [ 64 ]. However only two eligible MRI studies [ 37 , 38 ] were identified in our review, and all from China, therefore the data were not combined. The two studies found that MRI had both high sensitivity and specificity in detecting liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node size and enhancing lymph node status were used by all studies included in the review as the criteria to define malignancy. 29,30 The inability to identify metastatic lymph node status with normal size may explain the insufficient diagnostic accuracy of MRI. Although the diagnostic performance of MRI for N staging is not better than T staging, this imaging modality can also help clinicians to consider the risk of patients with lymph node metastatic disease to select suitable pre-operative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the pooled T (T3-4 vs T1-2) performance characteristics of MRI with DWI 9,22,24,25 to those without DWI 23,[26][27][28][29][30] to determine whether DWI could have helped preoperative staging performances (Table 4). However, we found that the summary results for T staging of GC (Table 4) showed no statistically significant difference between MRI with DWI and without DWI in sensitivity (p 5 0.279) and specificity (p 5 0.283).…”
Section: Subgroup Analysesmentioning
confidence: 99%